Marital crisis, imperativeness of the choice of law rule and Foreign Law - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The Spanish system of procedural treatment of foreign law is built on three main pillars: the one which sanctions the imperativeness of the choice of law rule, the rules on means of evidence, and the forecast of the consequences of the lack of evidence of such a law. The interaction of these pillars has has to be translated into differentiated responses according to the material sector of the Law in which we find ourselves. In matrimonial proceedings there is no room for the freedom of individuals, because of the strong public interests. Consequently, this means that the judicial body has to apply not only the conflict rule, but also the regulation claimed by it, even investigating it ex officio if it has not been brought by any of the parties. The only constrains are the respect of the right to an adversarial proceeding and the interdiction of the lack of defence.
Keywords: matrimonial causes; Foreign Law; mandatory application of the Choice of Laws Ru-les; EU Regulations